NEUROLOGICAL ADVERSE EVENTS FOLLOWING IMMUNIZATION (AEFI) ON HEALTH WORKFORCE OF A SECONDARY REFERRAL HOSPITAL IN SOUTH SULAWESI WHO RECEIVED THE - Lutpyah L; Arthur Hendrik Philips Mawuntu; Hamdana H; Mieke Actrees Hanna Nelly Kembuan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: The COVID-19 vaccination can relate to the occurrence of neurological adverse events following immunization (AEFI) that could impact work and daily activities. This problem is particularly important in the health workforce. However, little is known about neurological AEFI among the health workforce working in peripheral facilities. Objective: To study the neurological AEFIs and their impact among the health workforce who received the COVID-19 vaccination in a secondary referral hospital in South Sulawesi, the Andi Makassau Hospital (Rumah Sakit Umum Daerah Andi Makassau/RSAM). Methods: The COVID-19 pandemic, we created a questionnaire about neurological AEFIs and their effects which were distributed online using the Google Form application to the health workforce at the RSAM who had received at least one dose of COVID-19 vaccination. Results: We obtained 97 subjects. There were 78.5% neurological AEFIs with the most reported type being muscle pain (16%). Most neurological AEFIs were experienced by women (84.9%), age group 21-35 years (53.8%), and non-doctors/nurses (60.8%). The significant influencing factors in multivariate analysis were age group 36-45 years (p = 0.04), nursing proffesion (p = 0.005), and non- viral-based baccine type (p = < 0.0001). Conclusion: Neurological AEFI is commonly found among the health workforce who received the COVID-19 vaccination. However, it only has a little impact on their work and attitudes towards vaccination. This may be because all subjects experienced mild neurological AEFI.